Negotiation of new international health law on intellectual property, technology transfer, open science and pathogen access and benefit sharing: a textual and contextual analysis - Jeremy de Beer; Rosa De Koker (BMJ Public Health)
Introduction This original research article reframes new international law and policy developments at the intersections of open science, technology transfer, intellectual property and access and sharing the benefits of biomedical innovation in the context of global pandemics.Methods Through textual and contextual analysis, using the lens of national experiences and negotiating positions of one high-income country, Canada, it traces the evolution of legal normative developments from a proposed waiver of aspects of the World Trade Organisation Agreement on Trade-Related Aspects of Intellectual Property Rights through a forum shift to negotiate a new agreement for pandemic preparedness and response (the Pandemic Agreement) at the WHO.Results The analysis shows a significant evolution of treaty provisions on R&D, sustainable and diversified production of pandemic-related products, transfer of technology and know-how and access and benefit sharing. Juxtaposed against a Canadian parliamentary report, stakeholder consultations and Canada’s stated commitment to equity, the negotiating texts reflect major compromises on the key issues. High-income countries sought open access to pathogen gene sequence data crucial for pandemic prevention, preparedness and response while resisting measures other than voluntarily licensing on mutually agreed terms of private intellectual property rights derived from the use of such data or other publicly funded research. Low- and middle-income countries, meanwhile, were offered diluted language on technology transfer in exchange for a new pathogen access and benefit-sharing scheme.Conclusions The practical effects of these compromises remain to be seen, but they risk exacerbating rather than ameliorating global health inequities.